Effect of psychotherapy video on village health volunteers of primary care unit, Chaiwan hospital for burnout syndrome protection from COVID-19 outbreak situation - Leelawongkij, Aekachai; Khenkhum, Chananun (Journal of Preventive Medicine Association of Thailand, 2023)
The COVID-19 outbreak situation influenced medical staffs were at high workload and high risk for mental illness for 3 years ago. Due to high workload for a long time, village health volunteers were at high risk of burnout syndrome. Whereas there were restrictions of health resources and access to appropriate mental health care. Therefore, Innovative creation of psychotherapy video may be advantageous to accessibility of appropriate mental health care for burnout syndrome protection and maintaining the potency of village health volunteers in COVID-19 outbreak situation. This Quasi-experimental study aimed to 1) compare before&after results of psychotherapy video and group counseling therapy for burnout syndrome prevention in village health volunteers who were risk for burnout syndrome 2) compare mean difference results between psychotherapy video group and group counseling therapy for burnout syndrome prevention. Methods: The study populations were village health volunteers of primary care unit of Chaiwan hospital who were at risk for burnout syndrome from screening. 131 patients were included in this study. Maslach Burnout Inventory-Geneva Survey (MBI-GS) (Thai) screening test included data collected from pre-test and post-test burnout syndrome screening tests in 66 patients of psychotherapy video group and 65 patients of group counseling therapy group. Descriptive statistic was performed and reported in terms of counting number, percent, mean, standard deviation, median and interquartile range. Analytical statistics were also performed using T test, Wilcoxon signed-rank test, Mann-Whitney U test and Chi-square test. Result: There were 131 patients who attended psychotherapy. The factors such as sex, age group, graduate level were not significantly between test group and control group. 66 patients of psychotherapy video group and 65 patients of group counseling therapy group divided result into 3 aspects consisted of emotional exhaustion, cynicism, professional efficacy in both groups. After psychotherapy was completed in both groups, implemented 66 patients of psychotherapy video group and 65 patients of group counseling group revealed significantly improvement (p-value <0.05) by all of 3 aspects. Results of burnout syndrome protection were not significantly between test group and control group p-value =0.78, p-value =0.80 and p-value =0.36 by all of 3 aspects. Conclusion: This study suggested psychotherapy video effectively protected burnout syndrome in health care volunteers after fully of implementation.